2015
DOI: 10.7569/jrm.2014.634124
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly Mechanisms in Plant Cell Wall Components

Abstract: This review on self-assembly in biological fi brous composites presents theory and simulation to elucidate the principles and mechanisms that govern the thermodynamics, material science, and rheology of biological anisotropic soft matter that are involved in the growth/self-assembly/material processing of these materials. Plant cell wall, a multi-layered biological fi brous composite, is presented as a model biological system to investigate self-assembly mechanisms in nature's material synthesis. In order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…93 A similar approach has been applied to study domain formation in chiral assemblies of cellulose in plant cell walls. 94 In these models, the frustration free energy takes the Frank free energy of chiral nematic phase,…”
Section: Orientational Frustrationmentioning
confidence: 99%
“…93 A similar approach has been applied to study domain formation in chiral assemblies of cellulose in plant cell walls. 94 In these models, the frustration free energy takes the Frank free energy of chiral nematic phase,…”
Section: Orientational Frustrationmentioning
confidence: 99%
“…Since these surface ultrastructures with micro/nano scale features provide unique optical responses and iridescent colors [7][8][9][10][11], understanding their formation mechanism is crucial in realizing structural color in nature and in biomimetic design of novel photonic systems. As similar nano/micro scale periodic wrinkles are formed at the free surface of both synthetic and biological cholesteric liquid crystals (CLCs) [12,13], and CLC phases are widely found in Nature and living soft materials both in vivo and vitro [13,14], nematic liquid crystal self-assembly has been proposed as the formation mechanism of helicoidal plywoods and the surface ultrastructures in many fibrous composites ranging from plant cell walls to arthropod cuticles [15][16][17][18][19]. Moreover, it has been shown that the characteristics of chiral phases control the unique colors and optical properties exhibited in the films and fibers made by cellulose-based CLCs [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The assembling energies are frequently surface energy, magnetic or electric interactions. At the macroscopic scale, the assembling energy is often of magnetic origin (Gross and Dorigo, 2008), or mechanical connections (Penrose, 1959;Penrose and Penrose, 1957) and the source of disturbing energy can be tumbling (Boncheva et al, 2002;Gracias et al, 2000), shaking (Jacobs et al, 2002), stirring (Bowden et al, 1997;Terfort et al, 1997) or turbulent flow (Ilievski et al, 2011b;Murugesan et al, 2015;Roland et al, 1992;Zheng et al, 2004). Particles encounter each other in the provided energy landscape in order to self-assemble.…”
Section: Introductionmentioning
confidence: 99%
“…Particles self-assemble due to their mutual attraction and the disturbing energy in the environment. In macroscopic self-assembly the mutual attraction or assembling energy is frequently magnetic (Gross and Dorigo, 2008), and the disturbing energy turbulent flow (Ilievski et al, 2011b;Murugesan et al, 2015;Roland et al, 1992;Zheng et al, 2004). Turbulence is inherently random and chaotic and .…”
Section: Introductionmentioning
confidence: 99%